Cytoskeleton-Associated Protein 4, a Promising Biomarker for Tumor Diagnosis and Therapy - Li, Shuang-Xi; Li, Juan; Dong, Li-Wei; Guo, Zhi-Yong (Frontiers in Molecular Biosciences, 2021)
Cytoskeleton-associated protein 4 (CKAP4) is located in the rough endoplasmic reticulum (ER) and plays an important role in stabilizing the structure of ER. Meanwhile, CKAP4 is also found to act as an activated receptor at the cell surface. The multi-function of CKAP4 was gradually discovered with growing research evidences. In addition to the involvement in various physiological events including cell proliferation, cell migration and stabilizing the structure of ER, CKAP4 has been implicated in tumorigenesis. However, the role of CKAP4 is still controversial in tumor biology,which may be related to different signal transduction pathways mediated by binding to different ligands in various microenvironments. Interestingly, CKAP4 has been recently recognized as a serological marker of several tumors and CKAP4 is expected to be a tumor therapeutic target. Therefore, deciphering the gene status, expression regulation, functions of CKAP4 in different diseases may shed new light on CKAP4-based cancer diagnosis and therapeutic strategy. This review discusses the publications that describes CKAP4 in various of disease, especially on tumor promotion and suppression and provides detailed discussion on the discrepancy.